Development of Structured Assignment Sheets on Factors Affecting Reaction Rates to Train Concept Building Skills - Wullida Hayuning Bidari; Suyono (IJCER (International Journal of Chemistry Education Research), 2025)
The objective of this study is to develop a Structured Assignment Sheet for Concept Building Ability, abbreviated as LPT-KMK, that is feasible for use as a learning tool on the topic of factors influencing reaction rates. This research adopts a research and development (R&D) methodology to design and refine the LPT-KMK. The feasibility of the developed LPT-KMK is assessed based on three criteria: validity, practicality, and effectiveness. The LPT-KMK, which was developed and validated by expert reviewers, was trialed in June 2024 with a group of 25 eleventh-grade students from SMAS Muhammadiyah 10 Sugio, located in the Lamongan district. The instruments employed in this study included review sheets, validity assessment sheets, student response questionnaires, and concept-building ability tests. The findings indicate that the LPT-KMK achieved a mode score of 4 for both construct and content validity, classifying it as valid. Additionally, the practicality of the LPT-KMK was confirmed, with student response percentages ranging from 84% to 100%. The effectiveness of the LPT-KMK was validated through statistical analysis of student test results using the statistical application. The implementation of the LPT-KMK material on the topic of factors affecting reaction rates resulted in significant improvements in student performance. Therefore, the developed LPT-KMK is considered valid, practical, effective, and suitable for use as a learning device in chemistry education, specifically in teaching factors influencing reaction rates.